Management of Sepsis Patient with Multiple Trauma: A Case Report - Liliriawati Ananta Kahar; Talitha Azalia; Kornelis Aribowo (HM Publisher, 2022)
Background. In critically ill patient, source control surgery is one of the significant determinants of patient treatment and makes it successful. This case report was aimed to describe the management of sepsis patient with multiple trauma. Case presentation. A 20-year-old woman presented with blunt trauma in the chest, abdomen, and right superior and inferior extremities. After the surgical procedure, the patient was treated in the ward with skin traction and simple wound care; a week later, the wound became worse, abscess inside, necrotic tissue and smelled terrible, and the woman had fever and jaundice somnolence, and other clinical symptoms manifested and became sepsis. She underwent twice a debridement surgery for a nasty wound. After that, she was treated in intensive care. A multidisciplinary team was required to treat the patient. Conclusion. Surgical intervention, wound cleaning, and appropriate and adequate antibiotics are also given to prevent worsening sepsis in the future.